2009
DOI: 10.1590/s1413-70542009000300035
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy diagnosis, fetal quantification and gender estimation by ultra-sonography in ewes

Abstract: The objective of this experiment was to evaluate the accuracy of gestation, fetal sexing and quantification diagnoses in ewes. Pregnancy and fetal quantification were diagnosed in 105 ewes at 35 days of pregnancy. For the fetal gender diagnosis sexing diagnose 55 ewes between 49 and 59 days of pregnancy were used. All exams were recorded on DVD for posterior analysis. After birth, lamb sex was recorded to determine fetal sexing precision. Data were analyzed by chisquare ( 2 ) or Fisher's test, with a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
3
1
1
Order By: Relevance
“…However, sexing of female fetuses was more efficient in both evaluated periods (Table 6). This is contrary to the results obtained by Coubrough & Castell (1998) and Dias et al (2009), who reported higher efficiency in the diagnosis of male fetuses. Dias et al (2009) attributed the difference to the difficulty associated with the visualization of the GT when it was located near the tail, possibly due to poor fetal position and thus not allowing good images of the pelvic region.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, sexing of female fetuses was more efficient in both evaluated periods (Table 6). This is contrary to the results obtained by Coubrough & Castell (1998) and Dias et al (2009), who reported higher efficiency in the diagnosis of male fetuses. Dias et al (2009) attributed the difference to the difficulty associated with the visualization of the GT when it was located near the tail, possibly due to poor fetal position and thus not allowing good images of the pelvic region.…”
Section: Resultscontrasting
confidence: 99%
“…Of the 50 fetuses born, three were not diagnosed for fetal quantification on day 55 of gestation; however, on day 65, only one fetus was not diagnosed, these fetuses were from double gestations mistakenly diagnosed as single gestations. In this study, in accordance with the findings by Dias et al (2009), the accuracy of fetal quantification in single gestations was higher than in double gestations (Table 8). Depending on the period and type of gestation, it is not always possible to quantify or determine the sex of all fetuses in small ruminants.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Em ovelhas, o período para a completa de involução uterina é de aproximadamente 32 dias, mas pode variar de acordo com a raça e estação (HAYDER; ALI, 2008). (DIAS et al, 2009), mas especialmente no que se refere à dinâmica folicular, existe a necessidade de um bom treinamento, pois a anatomia da espécie dificulta o exame, limitando apenas a entrada do transdutor no reto da ovelha, sem o auxílio das mãos para direcioná-lo próximo aos ovários.…”
Section: Reconhecimento Materno E Fisiologia Da Gestaçãounclassified